2008
DOI: 10.2174/156720508785908946
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, Mitochondrial DNA and Alzheimers Disease. What Comes First?

Abstract: To date, the beta amyloid (Abeta) cascade hypothesis remains the main pathogenetic model of Alzheimer's disease (AD), but its role in the majority of sporadic AD cases is unclear. The mitochondria play central role in the bioenergetics of the cell and apoptotic cell death. In the past 20 years research has been directed at clarifying the involvement of mitochondria and defects in mitochondrial oxidative phosphorylation in late-onset neurodegenerative disorders, including AD. Morphological, biochemical and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 103 publications
(167 reference statements)
0
36
0
Order By: Relevance
“…Mitochondrial dysfunction has a certain impact on the pathogenesis of AD as indicated by impaired mitochondrial respiration observed in brain, platelets, and fibroblasts of AD patients (34). Energy failure, increased oxidative stress, and accumulation of Aβ could be caused by dysfunction of mitochondria, which would damage neurons and could explain many of the biochemical, genetic, and pathological features of sporadic AD (35).…”
Section: Mitochondrial Impairmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mitochondrial dysfunction has a certain impact on the pathogenesis of AD as indicated by impaired mitochondrial respiration observed in brain, platelets, and fibroblasts of AD patients (34). Energy failure, increased oxidative stress, and accumulation of Aβ could be caused by dysfunction of mitochondria, which would damage neurons and could explain many of the biochemical, genetic, and pathological features of sporadic AD (35).…”
Section: Mitochondrial Impairmentsmentioning
confidence: 99%
“…Studies found that puerarin had potent effects in improving learning and memory disorders induced by scopolamine or D-galactose in a mouse model (65). Yan et al reported that puerarin protected neurons against apoptosis in the cortex and hippocampus of AD rats caused by Aβ [25][26][27][28][29][30][31][32][33][34][35] through downregulating Aβ and Bax expression in brain tissues, therefore alleviating the spatial learning and memory impairment of diseased animals (66). The anti-AD effects of puerarin were also suggested to be related to its abilities in decreasing the lipid peroxidase levels and increasing superoxide dismutase levels in brain tissues, enhancing cerebral blood flow, and improving brain microcirculation (67,68).…”
Section: Puerarinmentioning
confidence: 99%
See 3 more Smart Citations